A palliative care goals model for people with dementia and their family: Consensus achieved in an international Delphi study - Nishimura, Mayumi; Harrison Dening, Karen; Sampson, Elizabeth L; Vidal, Edison Iglesias de Oliveira [UNESP]; Nakanishi, Miharu; Davies, Nathan; Abreu, Wilson; Kaasalainen, Sharon; Eisenmann, Yvonne; Dempsey, Laura; Moore, Kirsten J; Bolt, Sascha R; et al. (SAGE Publications, 2024)
Background: Advance care planning in dementia includes supporting the person and their family to consider important goals of care. International research reports the importance of psycho-social-spiritual aspects towards end of life. Aim: To develop a multidimensional international palliative care goals model in dementia for use in practice. Design: International Delphi study integrating consensus and evidence from a meta-qualitative study. The Delphi panel rated statements about the model on a 5-point agreement scale. The criteria for consensus were pre-specified. Setting/participants: Seventeen researchers from eight countries developed an initial model, and 169 candidate panellists were invited to the international online Delphi study. Results: Panellists (107; response 63.3%) resided in 33 countries. The model comprised four main care goals: (1) Comfort ensured; (2) Control over function maintained; (3) Identity protected and personhood respected and (4) Coping with grief and loss−person and caregiver supported. The model reflects how needs and care goals change over time with the progression of dementia, concluding with bereavement support. The first version of the model achieved a consensus after which it was slightly refined based on feedback. We did not achieve a consensus on adding a goal of life prolongation, and on use of the model by people with dementia and family themselves. Conclusion: A new palliative care goals model for people with dementia and their families includes relationship aspects for use by professionals and achieved a consensus among a panel with diverse cultural background. The position of life prolongation in relation to palliative care goals needs further research.
Keywords: advance care planning; biopsychosocial; cognitive disorders; Delphi technique; Dementia; interprofessional education; model; palliative care